Pengenalan Makanan Khas Tradisional Kinobo Sebagai Warisan Budaya Nusantara - Herman Sarumaha; Rini Yustika Wati Zai; Muhammad Aidil Huda; Seniman Ziliwu (Ilin Institute, 2024)
The aim of this community service is to increase the local community's insight into cultural heritage so that they can help preserve and protect it, instill cultural values in young people to love and be proud of their culture and encourage stakeholders to explore, develop and preserve local culture for the sustainable advancement of Indonesian culture. This community service is carried out to the form of workshop activities involving local communities and the Regional Goverment. In this workshop, the source person explains the material directly and then explores it in a discussion/question forum. The results of this community service show that the local community knows the essence of strengthening and preserving traditional specialties as valuable cultural heritage. The local community is quite aware that kinobo as a regional specialty food has opportunities for development that can be packaged into an economical product typical of the region as has been successfully done by other regions. This is a strategic step to encourage the cultural resilience of local communities and ensure the existence of traditional specialties amidst technological advances, increasingly modern community life and the rise of foreign cultures that can intervene in local culture.